Review:Studi perbandingan kandungan asam klorogenat pada Kop - Indrayani, Yosefin Putri; Habibur Umami Amrullah (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Coffee, being one of the most popular beverages in the world, is a rich source of chlorogenic acid. This review aims to determine the chlorogenic acid content of coffee. We reviewed from several journals about the antioxidants of coffee made. Of all the treatments in which the fermentation process was based on this condition, the concentration of chlorogenic acid increased with increasing fermentation time. The increase in the concentration of chlorogenic acid in Garut, Soreang, Aceh and Ciwidey green coffee beans obtained on day 18 was 13.17; 10.15am; 14.02 and 11.13% respectively